Computational Intelligence in Data Mining Proceedings of the International Conference on CIDM 2017 - Behera, Himansu Sekhar; Nayak, Janmenjoy; Naik, Bighnaraj; Abraham, Ajith (Advances in Intelligent Systems and Computing, 2019)
XXIX, 899 p. 478 illus., 272 illus. in color.